Luteolin protects against diabetic cardiomyopathy by inhibiting NF-κB-mediated inflammation and activating the Nrf2-mediated antioxidant responses - Li, Li; Luo, Wu; Qian, Yuanyuan; Zhu, Weiwei; Qian, Jianchang; Li, Jieli; Jin, Yiyi; Xu, Xuzhong; Liang, Guang (Phytomedicine (Stuttgart), 2019)
Diabetes mellitus is a well-known risk factor for the development of heart failure. Inflammation and oxidative stress play a key role in the development of diabetic cardiomyopathy (DCM), and this nexus represents an attractive target to combat this disease. Naturally occurring flavonoid luteolin exhibits both anti-inflammatory and antioxidant activities in various systems. In this study, we aimed to investigate potential cardioprotective effects of luteolin in cultured cardiomyocytes and in mice with type 1 diabetes. C57BL/6 mice were intraperitoneal injection of streptozotocin (STZ) to induce DCM. High glucose (HG) was used to induce H9C2 cells injury in vitro. Cardiac fibrosis, hypertrophy, inflammation and oxidative stress were studied both in vitro and in vivo. Our studies show that luteolin significantly reduces HG-induced inflammatory phenotype and oxidative stress in H9C2 cardiomyocytes. We found that the mechanisms involved inhibition of nuclear factor-kappa B (NF-κB) pathway and the activation of antioxidant nuclear factor-erythroid 2 related factor 2 (Nrf2) signaling pathway. Modulation of these pathways resulted in reduced expression of matrix proteins and cellular hypertrophy. Luteolin also prevented cardiac fibrosis, hypertrophy, and dysfunction in STZ-induced diabetic mice. These readouts were also associated with reduced levels of inflammatory cytokines and oxidative stress biomarkers. Our results indicate that luteolin protects heart tissues in STZ-induced diabetic mice through modulating Nrf2-mediated oxidative stress and NF-κB-mediated inflammatory responses. These findings suggest that luteolin may be a potential therapeutic agent for DCM. [Display omitted]